Linker and N-Terminal Domain Engineering of Pyrrolysyl-tRNA Synthetase for Substrate Range Shifting and Activity Enhancement - Jiang, Han-Kai; Lee, Man-Nee; Tsou, Jo-Chu; Chang, Kuan-Wen; Tseng, Hsueh-Wei; Chen, Kuang-Po; Li, Yaw-Kuen; Wang, Yane-Shih (Frontiers in Bioengineering and Biotechnology, 2020)
The Methanosarcina mazei pyrrolysyl-tRNA synthetase (PylRS)•tRNAPyl pair can be used to incorporate non-canonical amino acids (ncAAs) into proteins at installed amber stop codons. Although engineering of the PylRS active site generates diverse binding pockets, substrate ranges are found similar in charging lysine and phenylalanine analogues. To expand the diversity of ncAA side chains that can be incorporated via the PylRS•tRNAPyl pair, exploring remote interactions beyond the active site is an emerging approach in expanding genetic code research. In this work, remote interactions between tRNAPyl, the tRNA binding domain of PylRS, and/or introduced a non-structured linker between the N- and C-terminus of PylRS were studied. The substrate range of the PylRS•tRNAPyl pair was visualized by producing sfGFP-UAG gene products, which also indicated amber suppression efficiencies and substrate specificity. The unstructured loop linking the N-terminal and C-terminal domains of PylRS has been suggested to regulate the interaction between PylRS and tRNAPyl. In exploring the detailed role of the loop region, different lengths of the linker were inserted into the junction between N-terminal and C-terminal domains of PylRS to unearth the impact on remote effects. Our findings suggest that insertion of a moderate-length linker tunes the interface between PylRS and tRNAPyl and subsequently leads to improved suppression efficiencies. The suppression activity and substrate specificity of PylRS were altered by introducing three mutations at or near the N-terminal domain of PylRS (N-PylRS). Using a N-PylRS•tRNAPyl pair, three ncAA substrates, two S-benzyl cysteine and a histidine analogues, were incorporated into the protein site-specifically.